Precipitation Reaction Mechanisms of Mineral Deposits Simulated with a Fluid Mixing Model. (22nd February 2021) - Zhang, Yan; Han, Runsheng; Ding, Xing; Wang, Yurong; Wei, Pingtang
Abstract : Nonmagmatic, carbonate-hosted epigenetic hydrothermal Pb–Zn deposits similar to those at the Huize Pb–Zn Mine are widespread across the Sichuan–Yunnan–Guizhou (SYG) polymetallic province. The precipitation mechanisms of these geologically intriguing deposits are an area of interest for many researchers. To simulate the underlying precipitation reaction mechanisms and dynamics of each aspect, a fluid mixing model for metal sulfide precipitation was used in a series of experiments, where solutions that contain Pb/Zn chloride complexes and sulfide were subjected to pH changes, water-rock reactions, and dilutions. Based on the results of these experiments, thermodynamic phase diagrams, and other experimental findings, a fluid mixing genetic model was developed for SYG Pb–Zn deposits, and this model was used to analyze the mechanisms of metal sulfide precipitation. The results indicate that acidic fluids in the form of chloride complexes transported Pb and Zn, whereas sulfide exists in the form of H2 S within these fluids. The precipitation of metal sulfides occurs when these fluids undergo changes in pH, water-rock reactions, or isothermal dilution. The pH changes were found to be the most effective method for the induction of sulfide precipitation, followed by dilution and then water-rock reactions. The formation of sulfide precipitates due to pH changes, water-rock reactions, and dilution can be attributed to a single mechanism, i.e., changes in the pH of the fluid. Therefore, changes in pH are the primary mechanism of sulfide precipitation.